KEBERHASILAN OKULASI DARI BERBAGAI PROVENANS DAN VARIETAS JATI (Tectona grand is) (Results of Bud Grafting trom Various Provenance and Varieties of Teak (Tectonagrandis) - , Adriana ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
Some teak types are believed of genetic constitution while others are geographical. Their differences may be seen from their wood properties or they stem morphology. Jati Kapur, Jati Minyak, and Jati Dorengarediscriminatedbasedonteakwood properties. Meanwhile, Jati Knobel and Jati Gladstam are recognized from their stem morphology. Recognizable variation is observed, however, in some teak provenances. In addition. distinct teak types, presumably correspond to teak varieties. All these teak types belong to the same species: Tectonagrandis L.f..However, different species of Tectonagenus is found, namely. Tectonahamiltoniana Wall.Ex Schau. With such ample variation, related to either provenance or variety, it is of high interest to study their graftability variation. The specific objective of the study was to ascertain the successful rate of bud grafting from a number of provenances and varieties. The study concluded that successful grafting percentage was suffient!y high for all seedlots of Tectonagrandis. while Tectonahamiltoniana showed only 90 % successful rate.